ACID RESISTANCE, ELECTROPHORETIC MOBILITY OF THE RED CELLS AMONG THE NEWBORN CHILDREN WITH THE SEVERE RESPIRATORY DISTRESS SYNDROME - E.N. Serebryakova; D.K. Volosnikov; S.L. Sashenkov ("Paediatrician" Publishers LLC, 2007)
Respiratory distress syndrome is one of the main reasons of the high risk morbidity and lethality among the newborn children in early neonatal period. The aim of the present research is to study the acid resistance and electrophoretic mobility of the red cells among the term infants with severe respiratory distress syndrome. The results of the research showed that among the newborn children with severe respiratory distress sync dome (n = 41) the electrophoretic mobility of the red cells is reduced, while the acid resistance is increased, which speaks of the disorder in the functional activity of the red cells and tension of erythrogenesis in the given group of the newborn children if compared with 44 children without distress syndrome.Key words: newborn children, respiratory distress syndrome, red cells, acid resistance of the red cells, electrophoretic mobility of the red cells.